2014
DOI: 10.1002/chem.201404309
|View full text |Cite
|
Sign up to set email alerts
|

Strong Interplay between the Electron Spin Lifetime in Chemically Synthesized Graphene Multilayers and Surface‐Bound Oxygen

Abstract: The electron spin lifetime in an assembly of chemically synthesized graphene sheets was found to be extremely sensitive to oxygen. Introducing small concentrations of physisorbed O2 onto the graphene surface reduced the exceptionally long 140 ns electron spin lifetime by an order of magnitude. This effect was completely reversible: Removing the O2 by using a dynamic vacuum restored the spin lifetime. The presence of covalently bound oxygen also decreased the electron spin lifetime in graphene, although to a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Kochan et al proposed theoretically that short (100 ps) spin relaxation times in graphene could be partially due to resonant scattering of electrons by local magnetic moments. This resonant scattering mechanism is in qualitative agreement with experimental ESR observations of the detrimental effect of surface bound oxygen on the graphene electron spin lifetime . Sosenko et al showed that spin valve and Hanle spin precession experiments suffered from additional spin loss due to the resistance mismatch between ferromagnetic electrodes and graphene, and not for instance, Coulomb scattering .…”
Section: Graphenesupporting
confidence: 84%
See 1 more Smart Citation
“…Kochan et al proposed theoretically that short (100 ps) spin relaxation times in graphene could be partially due to resonant scattering of electrons by local magnetic moments. This resonant scattering mechanism is in qualitative agreement with experimental ESR observations of the detrimental effect of surface bound oxygen on the graphene electron spin lifetime . Sosenko et al showed that spin valve and Hanle spin precession experiments suffered from additional spin loss due to the resistance mismatch between ferromagnetic electrodes and graphene, and not for instance, Coulomb scattering .…”
Section: Graphenesupporting
confidence: 84%
“…Atom colors represent carbon (black/grey), oxygen (red), hydrogen (white), and nitrogen (green). Reproduced with permission . Copyright 2015, Wiley‐VCH.…”
Section: Graphenementioning
confidence: 99%
“…The EPR technique provides detailed microscopic information about the oxidation state and the local environment of the paramagnetic ions present in the crystal down to ppm levels [44,57,58,59,60,61,30,62]. Furthermore, multi-frequency EPR measurements offer a better insight into the interactions, and high-frequency EPR measurements yield more detailed spectroscopic information [63,64,65,66,67,68,69]. Figure 4 shows the EPR spectra of both samples taken at 50 K at 9.4 GHz (a) and at 105 GHz (b).…”
Section: Resultsmentioning
confidence: 99%
“…Being significantly influenced by adsorption of various atoms and molecules [16,17], localization process is a crucial issue in the physics of graphene when considering its application in multiple areas such as energy storage, molecule sensing, photovoltaics, and nanoelectronics. This phenomenon can be well observed using the electron paramagnetic resonance (EPR).…”
Section: Introductionmentioning
confidence: 99%